Perpustakaan Islam di Malaysia masa kini - Suja', Balqis (JAKIM, 2013)
The paper describes emergence of Islamic libraries and discusses factors that contribute to the establishment of Islamic libraries and the ways it can be used in the Malaysia context. Islamic libraries, originated ... Generally, Malaysian mosque libraries are sustaining themselves through the motivation of the Muslim community to restore the function of mosques as learning nodes. Malaysian Islamic libraries are growing in number with some of them are in good shape to emerge being the best in the region.